Design of sequencing medium access control to improve the performance of wireless networks - Krishna, P. Venkata (Array, 2008)
This paper presents a technique known as sequencing on MAC layer for wireless networks. MAC layer issues are very important while acceding channel over wireless networks. Normally, communication uses RTS/CTS mechanism to access channel for transmission of data. Mostly, it is observed that RTS/CTS handshake may introduce some delay especially in case of wireless networks. Hence, a sequencing method is proposed where selected RTS packets are dropped voluntarily to improve overall throughput of the network although individual performance of the transmissions is reduced